Is charity a missing link in sustainable development? - Whitmore, Lawrence (European Journal of Sustainable Development, 2025)
This paper examines the moral virtue of charity and its importance in building a just, peaceful and sustainable society. While acts of charity in the form of donations play an important role in a circular economy—reducing the demand for natural resources and alleviating poverty—the moral virtue of charity as the selfless desire to do good for others inclines individuals in a broader sense to have goodwill toward each other, put aside their differences, coexist peacefully and support each other in times of trouble. The study explores how charity is viewed in different cultures and traditions, how it can be extended to include all living beings, and how love, empathy and compassion can work together to ease suffering and hardship, enhance social justice, and build resilient societies. Charity as a moral virtue empowers individuals to effect positive change and can help transform society from self-centered, destructive and overconsuming to benign, peaceful, just, and sustainable. Keywords: morality, virtue ethics, charity, culture of charity, sustainable development, moral philosophy.